Career anchors and the effects of downsizing: implications for generations and cultures at work. A preliminary investigation - Marshall, Verena; Bonner, Dede (Emerald Group Publishing Limited, 2003)
This paper examines the relationships between career anchors, age, culture, gender, employment experience and the impact of downsizing on career planning. Presents the results drawn from 423 graduate business students in Australia, the USA, Malaysia, South Africa and the UK. Aims to explore Schein’s contention that employees develop a self-concept or career anchor that holds their “internal career” together even as they experience a dramatic change in their “external career” that leads to greater self-discovery. Previous studies have examined differences in career orientations in Europe, the USA and the UK. This research allows examination of the distribution of career anchors within a multi-cultural sample across age groups, gender, culture and work experience. The data also enable investigation of the relationship between career anchors and reported impact of organisational downsizing on career decisions.